Phase I safety, pharmacokinetic, and pharmacogenomic trial of ES-285, a novel marine cytotoxic agent, administered to adult patients with advanced solid tumors - Baird, Richard D.; Kitzen, Jos; Clarke, Paul A.; Planting, Andre; Reade, Sarah; Reid, Alison; Welsh, Lyndsey; López Lázaro, Luis; de las Heras, Begona; Judson, Ian R.; Kaye, Stan B.; Eskens, Ferry; et al. (Molecular cancer therapeutics, 2009)
A dose-escalation, phase I study evaluated the safety, pharmacokinetics, pharmacogenomics, and efficacy of ES-285, a novel agent isolated from a marine mollusc, in adult cancer patients. Patients received a 24-hour i.v. infusion of ES-285 once every 3 weeks until disease progression or unacceptable toxicity. The starting dose was 4 mg/m 2 . Dose escalation in cohorts of at least three patients proceeded according to the worst toxicity observed in the previous cohort. Twenty-eight patients were treated with 72 courses of ES-285 across eight dose levels. No dose-limiting toxicities were seen between 4 and 128 mg/m 2 . Two of four patients treated at 256 mg/m 2 had dose-limiting reversible grade 3 transaminitis; one patient at 256 mg/m 2 also had transient grade 3 central neurotoxicity. One of three patients subsequently treated at 200 mg/m 2 died following drug-related central neurotoxicity. Other toxicities included phlebitis, nausea, fatigue, and fever. Pharmacokinetic studies indicated dose proportionality with high volume of distribution (median V ss at 256 mg/m 2 was 2,389 liters; range, 1,615–4,051 liters) and long elimination half life (median t 1/2 at 256 mg/m 2 was 28 h; range, 21–32 h). The three patients with dose-limiting toxicity had the highest drug exposure. Pharmacogenomic studies of paired surrogate tissue samples identified changes in gene expression following treatment that correlated with increasing dose. Disease stabilization for 6 to 18 weeks was recorded in nine patients. Using this schedule, 128 mg/m 2 was considered safe and feasible. At this dose, pharmacologically relevant concentrations of the drug were safely achieved with pharmacogenomic studies indicating changes in the expression of genes of potential mechanistic relevance. [Mol Cancer Ther 2009;8(6):1430–7]